Comparison of Dual β-Lactam therapy to penicillin-aminoglycoside combination in treatment of Enterococcus faecalis infective endocarditis. Issue 5 (November 2018) - El Rafei, Abdelghani; DeSimone, Daniel C.; Narichania, Aalap D.; Sohail, M. Rizwan; Vikram, Holenarasipur R.; Li, Zhuo; Steckelberg, James M.; Wilson, Walter R.; Baddour, Larry M.
Summary: Background: Dual β-lactam therapy and a penicillin-aminoglycoside combination are first line regimens in the treatment of penicillin-susceptible Enterococcus faecalis infective endocarditis (EFIE). Our aim was to compare ampicillin plus ceftriaxone (A+C) to ampicillin plus gentamicin (A+G) in the treatment of EFIE. Methods: This was a retrospective cohort study of adults (≥18 years) patients diagnosed with EFIE at Mayo Clinic campuses in Rochester, Minnesota, and Phoenix, Arizona and treated with either A+C or A+G. Main outcome measurements were 1 year mortality, nephrotoxicity, and EFIE relapse rates. Results: Eighty-five cases of EFIE were included in this investigation. The majority ( n =67, 79%) of patients received A+G while 18 (21%) patients received A+C as initial treatment. On admission, patients who received A+C had a higher Charlson Comorbidity Index (median [IQR], 4 [3, 4 vs. 2 [1, 4]; P =.008) and a higher baseline serum creatinine (median [IQR], 1.2 [0.9, 1.6] vs. 0.9 [0.8, 1.2] mg/dL, P=.020 ). The 1 year mortality rates were similar for both treatment groups, 17% vs. 17%, P =.982. Each group had 1 case of relapsing EFIE. Patients who received A+G had worse kidney function outcome demonstrated by a greater increase in serum creatinine at end of therapy (median [IQR] difference, +0.4 [0.2, 0.8] vs. -0.2 [−0.3, 0.1] mg/dL, P ≤.001). Conclusion: A+C appears to be a safe and efficacious regimen in the treatment of EFIE. Patients treated with A+C had lower rates of nephrotoxicity and no differences in relapse rate and 1-year mortality as compared to that of the A+G group.